EFEKTIVITAS ANKLE SUPPORT TERHADAP KESEIMBANGAN DINAMIS PADA PEMAIN FUTSAL NON PROFESSIONAL DENGAN CEDERA PERGELANGAN KAKI - Anissa Eka Septiani (Tahta Media Group, 2024)
Background: Ankle injury is a common condition experienced by individuals who have high activity or in individuals who exercise. This condition causes pain, swelling, instability, muscle weakness, postural control deficits, and balance disorders. Efforts to improve dynamic balance include providing ankle support that increases proprioception for the user. Purpose of the study: to determine the effectiveness of using ankle support on dynamic balance in nonprofessional futsal players with ankle injuries. Research method: using quantitative quasi experiment, one group pretest posttest design with a total of 25 subjects of nonprofessional futsal players who experienced injuries. Analysis of this research data using the Wilcoxon test The results of the hypothesis test showed a p value of 0.000 and the value <0.05, meaning that there is an effectiveness in providing ankle support to improve dynamic balance in nonprofessional futsal players with ankle injuries. Conclusion: ankle support is effective in improving balance for nonprofessional futsal players with ankle injuries.